Situation Report: Czechoslovakia, 28 August 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Communique of the Meeting of Polish and Czechoslovak Dissidents / by Vladimir Sobell Religious Action and Reaction Prisoners of Conscience in Times of "Restructuring" The Night Congress of the Czechoslovak Journalists' Union / by Jan Palec Drug Abuse / by Jan Obrman Apprentices and Young Workers / by Jan Palec; Jan Obrman